2012
DOI: 10.1007/s10522-012-9394-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking of structural proteins in ageing skin: an in situ assay for the detection of amine oxidase activity

Abstract: With increasing age, dynamic tissues such as lungs, blood vessels and skin lose their ability to both deform and recoil, culminating in tissue stiffening. This loss of tissue elasticity, which profoundly impacts tissue function and thus morbidity, may be due not only to changes in the relative abundance of key extracellular matrix proteins within tissues but also to their accumulation of post-translational modifications. Whilst to date attention has focussed primarily on the age-related non-enzymatic formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
2
14
0
1
Order By: Relevance
“…This result might be explained by several studies, which reported that the activity of LOX family was higher in the aged group than in the young group in skin [36,37].…”
Section: Discussionmentioning
confidence: 84%
“…This result might be explained by several studies, which reported that the activity of LOX family was higher in the aged group than in the young group in skin [36,37].…”
Section: Discussionmentioning
confidence: 84%
“…2). Collagen cross-linking can either be induced enzymatically via lysyl oxidase enzymes or chemically as a result of advanced glycation end products formation (Langton et al, 2013). The later modification was shown to trigger pathological age-related tissue stiffening (Sherratt, 2009).…”
Section: Urinary Proteomementioning
confidence: 99%
“…An agerelated stiffening of tissue was observed in tendon, vascular and myocardial tissue, cartilage and skin. 9,10,18,43 A stiffening of tissue was also observed in diabetic volunteers. A notable in vitro study reported an increase in stiffness of rabbit tendon incubated with glucose.…”
mentioning
confidence: 80%
“…5 With elastin turnover approaching a lifespan, structural and physiochemical changes to the elastin network accumulate with age. 9,10 Decorin and versican undergo changes in their GAG chains, with studies showing a reduction in the molecular size of their polysaccharide chains. 6,11 HLA content in the dermis decreases as it is produced less by fibroblasts and disappears altogether in the epidermis as a function of age.…”
Section: Ahmed Et Almentioning
confidence: 99%
See 1 more Smart Citation